Harnessing the Antibacterial Properties of Fluoridated Chitosan Polymers against Oral Biofilms - Dien Puji Rahayu; Roger Draheim; Aikaterini Lalatsa; Marta Roldo (MDPI AG, 2022)
Dental caries are a worldwide endemic chronic disease affecting people of all ages. Due to the limitations of daily used oral hygiene products, there is an unmet need for new, effective, safe, and economic oral products. We have recently demonstrated that N-(2(2,6-diaminohexanamide)-chitosan (CS3H Lys) has enhanced antibacterial properties against Streptococcus mutans, the main cariogenic bacterium, and here we investigated the effect of fluoridation of this polymer (CS3H Lys F) on its antibacterial properties and the ability to protect teeth from acid demineralization. We further formulated this polymer into mouthwash preparations and studied their cytocompatibility and physicochemical stability over 6 months. CS3H Lys F was 1.6-fold more effective than the highest tested oral NaF dose in preventing acid demineralization. CS3H Lys F has a 3- to 5-fold lower minimum inhibitory concentration value against S. mutants than the values reported for chitosan polymers and showed negligible cell toxicity. The mouthwashes were stable at both 25 and 40 °C. Further work is under way towards other CS3H Lys F oral hygiene products such as a toothpaste.